The THE ROLE OF E-BOOKS IN LEARNING PHYSICS: LITERATURE REVIEW - Lidiawati, Mutiara Putri Yaldi (Physics Learning and Education, 2024)
Currently the world is entering an era of globalization which is characterized by the utilization of the role of Information and Communication Technology (ICT) in various aspects of life. Advances in Information and Communication Technology (ICT) facilitate access to information for anyone and anywhere, this encourages changes in various aspects of life, one of which is education.Advances in technology that are increasingly developing in the world of education require teachers to be more creative in integrating this technology into learning. One of them is by utilizing electronic teaching materials, such as e-books in learning. E-book stands for "electronic book" referring to a book available in digital format that can be read electronically and contains text or image content for learning.This study aims to analyze the role of e-books in learning Physics.This research was written using a qualitative methodology and data was collected through a literature review approach to national and international journals on the use of e-books in physics learning which were published in the last 10 years through the Sinta, Garuda, Google Scholar, and ScienceDirect databases. The sample used was 39 journal articles. Research shows that e-books can increase students' interest, motivation and enthusiasm in learning, increase independence, learning outcomes, conceptual understanding, problem solving, learning achievement, 4C skills (Communication, Collaboration, Critical Thinking and Creativity Thinking) and increase participant representation students in physics learning. It can be concluded that the use of e-books as an alternative learning material is beneficial for students.